Transanal protrusion of intussusception can be sign of Waugh syndrome - Noviello Carmine; Cascone Salvatore; Romano Mercedes; Nobile Stefano; Papparella Alfonso (Elsevier, 2022)
Intussusception rarely occurs with transanal prolapse of intussusception (TAPI), this presentation may be a sign of Waugh's syndrome (WS), an association between intestinal malrotation and intussusception. The authors present the case of infant with an episode of TAPI, resolved with air enema, who required later diagnostic tests that showed the presence of WS, for which surgery was required after the resolution of the intussusception. At now we found only 72 cases reported of WS and some of them clinically presented with TAPI. In our opinion, patients with this type of presentation require a thorough radiological study of the intestine to rule out intestinal malrotations.